Catastrophic Zone I Open Globe Injury: Pathophysiological Insights and Staged Surgical Triumphs in a Case of Corneal Rupture, Lens Extrusion, and "Blackball" Hyphema - Harrie Kurnia Rahman; Fitratul Ilahi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Complex open globe injuries (OGIs) involving the simultaneous destruction of multiple anterior segment structures represent a formidable challenge in ophthalmic traumatology. These injuries necessitate a staged surgical approach to restore ocular integrity and optimize the potential for visual rehabilitation. Case presentation: A 44-year-old male presented with a severe Zone I OGI in the left eye from a high-velocity projectile stone. His initial best-corrected visual acuity was limited to light perception. Examination revealed an 8-mm corneal rupture with uveal prolapse, complete anterior extrusion of the crystalline lens, and a Grade IV "blackball" hyphema. The Ocular Trauma Score (OTS) was calculated as 1, predicting a very poor visual outcome. Immediate primary repair involved anterior vitrectomy, lensectomy, hyphema evacuation, and corneal suturing. After a six-month stabilization period, a secondary scleral-fixated intraocular lens (IOL) was implanted using a double-needle Yamane technique. Conclusion: Despite the devastating nature of the initial injury and a grim prognosis as per the OTS, a principled, staged surgical strategy resulted in a final best-corrected visual acuity of 20/50. This case highlights that adherence to damage-control principles—prioritizing anatomical restoration in the primary surgery and deferring refractive correction—can lead to unexpectedly favorable functional outcomes in the most severe categories of ocular trauma.